2010
DOI: 10.1016/j.jcrs.2009.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and flap dimensions of a new femtosecond laser for laser in situ keratomileusis

Abstract: Overall, the flap dimensions and refractive results were predictable and the complication rate was acceptable after LASIK using the new femtosecond laser for flap creation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…A study reported that flap dimensions and refractive results of LASIK using the Femto LDV were predictable, with an acceptable rate of complications and that no eyes had significant losses in CDVA at 6 months postop 28. Likewise, the predictability and accuracy of the IntraLase for flap creation, when compared to a microkeratome, were reported 29.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that flap dimensions and refractive results of LASIK using the Femto LDV were predictable, with an acceptable rate of complications and that no eyes had significant losses in CDVA at 6 months postop 28. Likewise, the predictability and accuracy of the IntraLase for flap creation, when compared to a microkeratome, were reported 29.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in other studies. [30][31][32] Table 3 shows the complications in other studies using the VisuMax or another femtosecond laser platform. 14,18,27,[31][32][33][34] Most of these studies were performed during the learning phase of the procedure, and the rate of complications will decline gradually over time.…”
Section: Discussionmentioning
confidence: 99%
“…Current ANSI laser safety standards for femtosecond NIR pulses cover accidental exposures of the eye and skin to pulsed irradiation in terms of immediate damage, rather than a systematic planned exposure of tissue and any resulting long term effects. The research literature contains limited reports on the safety of NIR ultrashort laser pulses in humans, with the majority being related to the use of femtosecond laser pulses in the eye (e.g [14]. ) due to the increased use of femtosecond ablation in Lasik surgery.…”
Section: Introductionmentioning
confidence: 99%